2009
DOI: 10.1097/mot.0b013e32832c6a1d
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing dendritic cells for the induction of transplantation tolerance

Abstract: The use of DC to induce antigen-specific tolerance by tapping into the Treg network remains a viable prospect for future strategies for immune intervention in allograft rejection. Furthermore, principles learned from the study of whole organ transplantation may find application in the emerging field of regenerative medicine, in which the use of immune suppression is likely to be contraindicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…Their ability to induce both immunogenic and tolerogenic immune responses has made them interesting tools for treatment of infections, cancer, autoimmune diseases, and allograft rejection (8). Much research has focused on the active manipulation of DCs, either to augment favorable immunity or to suppress unwanted immune activation (9)(10)(11)(12)(13)(14). Also pathogens and tumors often escape immunity via modulation of DC immunogenicity (15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…Their ability to induce both immunogenic and tolerogenic immune responses has made them interesting tools for treatment of infections, cancer, autoimmune diseases, and allograft rejection (8). Much research has focused on the active manipulation of DCs, either to augment favorable immunity or to suppress unwanted immune activation (9)(10)(11)(12)(13)(14). Also pathogens and tumors often escape immunity via modulation of DC immunogenicity (15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…In utero cell transplantation is one such approach that is being tried in order to achieve central tolerance (Fisher et al, 2013;Hayashi et al, 2002). The induction of peripheral tolerance targets peripheral T-cells typically using either costimulatory blockade (e.g., anti-CD154 and CTLA4-Ig), by transferring/inducing Treg cells, or by utilizing tolerogenic dendritic cells (Chandrasekharan et al, 2013;Issa and Wood, 2012;Leishman et al, 2011;Boyd and Fairchild, 2010;Long and Wood, 2009;Silk and Fairchild, 2009;Waldmann et al, 2008;Cobbold et al, 2006). The induction of peripheral tolerance targets peripheral T-cells typically using either costimulatory blockade (e.g., anti-CD154 and CTLA4-Ig), by transferring/inducing Treg cells, or by utilizing tolerogenic dendritic cells (Chandrasekharan et al, 2013;Issa and Wood, 2012;Leishman et al, 2011;Boyd and Fairchild, 2010;Long and Wood, 2009;Silk and Fairchild, 2009;Waldmann et al, 2008;Cobbold et al, 2006).…”
Section: Modulation Of Host Immunitymentioning
confidence: 99%
“…Despite enthusiasm to exploit tolerogenic DC clinically [1][2][3], what constitutes a tolerogenic DC in vivo, and how it achieves tolerance, is still poorly understood. Immunological outcome was thought to be related directly to the maturation status of DC, with immature DC presenting for tolerance [4][5][6]; however, this simple view rapidly failed to account for accumulating experimental observations [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…DC in vitro to generate maturation-resistant cells for adoptive cell therapy [2,9]; however, attempts to induce tolerance to allografts in conventional models have generally failed unless combined with other immunosuppressive agents [1], necessitating a move to reductionist models. We previously showed that we could induce tolerance to male skin grafts in female TCR transgenic A1.RAG mice by transferring either ''immature'' BMDC or BMDC modulated using 1a, 25-dihydroxyvitamin D 3 , (BMDC-VD3), but only the modulated cells retained their capacity to induce tolerance after maturation with the TLR4-ligand LPS [17].…”
mentioning
confidence: 99%